2012
DOI: 10.1007/s12471-012-0339-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise test predicts sustained ventricular arrhythmias in chronic heart failure

Abstract: CPX provides prognostic independent information for risk of SVA in subjects with CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Our results show that low peak VO2 is associated with a long-term occurrence of MVA. These results are similar to findings of Correale et al (2013, 36-43), they found that patients with heart failure and episodes of sustained ventricular tachycardia had lower peak VO2 values [17].…”
Section: Discussionsupporting
confidence: 92%
“…Our results show that low peak VO2 is associated with a long-term occurrence of MVA. These results are similar to findings of Correale et al (2013, 36-43), they found that patients with heart failure and episodes of sustained ventricular tachycardia had lower peak VO2 values [17].…”
Section: Discussionsupporting
confidence: 92%
“…Patients underwent pulmonary and cardiology assessment by clinical examination and assessed by CPET and RHC as reported elsewhere . Medical history, heart rate, systolic blood pressure, body mass index, NYHA class and medications were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…As for many chronic diseases, however, the correlations between symptoms and the degree of cardiac impairment at rest, and between symptoms and disease prognosis, are poor in patients with HF [3]. Indeed, our understanding of the exact mechanisms of progressive intolerance to exercise is far from complete.…”
Section: Introductionmentioning
confidence: 99%